Bolaamphiphilic microstructural polyphenol flavonoids as sustainable high efficacy coating for aluminium surface in aqueous solution. (4th August 2022) - Fares, Mohammad M.; Radaydeh, Samah K.; Masadeh, Khansa'a H.
Abstract: Bolaamphiphilic polyphenol flavonoids were successfully revealed as a sustainable coating at the solid/liquid interface of an aluminium surface in an aqueous solution. Polyphenol flavonoids extracted from brown onions demonstrated the presence of bolaamphiphiles above 600 ppm. Characterization of the polyphenol flavonoids coating was performed using spectroscopic 1 H‐nuclear magnetic resonance and attenuated total reflectance Fourier‐transform infrared techniques for chemical identification, UV–vis and optical microscopy techniques were used for bolaamphiphilic microstructures assessment, and a scanning electron microscope was used for the assessment of surface morphology. Variant operating conditions used to show best coating efficacy were as follows: concentration = 600 ppm, solution pH = 10 in the presence of PO4 3− ion cross‐linker, operating temperature = 10°C, microwave pre‐irradiation time = 5 s, and turbulent flow of the solution = 300 rpm. Maximum coating efficacy showed a coating efficacy of 97%. The suitability of several adsorption isotherms, like Langmuir, Temkin, and Freundlich, was tested to fit our data. Equilibrium constant values were in favour of successful coating, especially at lower temperatures (20°C). Spontaneous (negative Δ G °) and high affinities of coating material to the surface were revealed from thermodynamic parameters (Δ H ° and Δ S °). Conclusively, such research is meant to emphasize our continuous support for the use of plant waste in artificial sectors such as coating of metals, and for their economic feasibility and low cost as high efficacy renewable materials. Abstract : Natural polyphenol flavonoids as sustainable high efficacy coating over the aluminium surface.